Experimental Evaluation of the Efficiency of Methods for Final Disinfective Treatment of Premises of the Large isolated Zones used for Work with Pathogenic Agents when Conducting Works with the Smallpox Virus - O. P. Os’kina; V. V. Zolin (Проблемы особо опасных инфекций, 2018)
Objective. Determination of the effectiveness of final disinfection treatment of virological laboratory rooms (with the passageway room between two entries) in the isolated zone used for work with pathogenic agents, of the maximum containment laboratory by fumigation with formaldehyde vapors, including the assessment of the optimal amount of formalin. Experimental evaluation of the suitability of the aerosol generator “Ultrasprayer P-60” for the final disinfection of the premises of the “contagious” zone with the “dry steam” of hydrogen peroxide. Materials and methods. The effectiveness of the final disinfection of the surfaces in the premises of the “infectious” zone of the maximum containment laboratory was evaluated using cambric test objects contaminated by the spore-forming test-culture B. thuringiensis. Results and discussion. As a result of experimental studies, the required amount of formalin was determined that is sufficient to completely inactivate possible infectious contaminants that may be potentially located on the surfaces of equipment and rooms located in the “contagious” zone of the maximum containment laboratory, during fumigation with formaldehyde vapors. The amount of formalin specified experimentally turned out to be 1.4 times more than the recommended by regulatory documentation for unventilated rooms, but 2-2.5 times less than that used for final disinfection of maximum containment laboratory previously. Disinfection treatment of the premises and equipment located in the “contagious” zone of the laboratory with 6 % hydrogen peroxide “dry steam”, which is the active agent of Disargent drug, sprayed through the «Ultrasprayer р-60» aerosol generator, was more effective than spray irrigation with 6 % hydrogen peroxide aerosol generated using pneumatic aerosol nozzles. At the same time, it was possible to achieve sufficiently complete inactivation of the test microorganism located on test objects at a concentration of 1·106 cells/cm2, by increasing the concentration of hydrogen peroxide sprayed by the device up to 10 %. However, even in that case, viable test microorganisms remained in the hidden cavities of the equipment and office machinery, which makes further studies relevant to establish the optimal concentration of hydrogen peroxide during the final disinfection with an «Ultrasprayer р-60» aerosol generator or similar equipment from other manufacturers.